MRI Findings of Non-Degenerative Pathoanatomical Changes in Low Back Pain - Karki, Dan B; Panta, Om B; Gurung, Ghanshyam (Nepal Journal of Neuroscience, 2016)
Non-degenerative pathoanatomical changes are far less common than degenerative changes but benefi ts most from imaging assessment. This study aimed to evaluate the non-degenerative pathoanatomical changes in patients undergoing MRI for low back pain. The study was a retrospective study conducted for the duration of 3 years in a multimodality-imaging center. All patients undergoing MRI of lumbosacral spine with complains of low back pain with or without radiculopathy were assessed for morphological changes and other abnormal fi ndings. After excluding patients with degenerative changes, non-degenerative pathologies were evaluated. Data was entered in predesigned proforma and analysis was done with SPSS 21.0. There were 183 patients who met the inclusion criteria and were included in the study. The mean age of the patients was 51.23 ±16.86 years. Compression fracture of the vertebra was the most common non-degenerative changes accounting for 34% cases followed by spinal meningeal cysts (26%) and infection (14%). Fractures were more common in upper lumbar level as compared to lower lumbar levels. Meningeal cysts were noted to involve the sacral spinal canal more frequently followed by lower lumbar levels. Infective lesions were equally distributed throughout the lumbar spine. Hemangioma was common lesion involving 16% of cases. Lumbosacral transitional vertebra was seen in 7(3.8%) patients. The common non-degenerative pathoanatomical changes associated with low back pain were traumatic lesion, infection, neoplastic lesion and lumbosacral transitional vertebra. Nepal Journal of Neuroscience 12:59-62, 2015